Emission brightness, photon yield, and radiation losses of ultrarelativistic electrons in oriented thick crystals - Amosov K. Yu.; Vnukov I. E.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sarychev V. P. (1991, 1991)
Title screen